Thoracoscopic pleural biopsy improves yield of Xpert MTB/RIF for diagnosis of pleural tuberculosis. Issue 7 (27th February 2018) - Christopher, Devasahayam J.; Dinakaran, Sridevi; Gupta, Richa; James, Prince; Isaac, Barney; Thangakunam, Balamugesh
ABSTRACT: Background and objective: Extrapulmonary tuberculosis (EPTB) accounts for 15% of all TB patients, and TB pleural effusion is the second most common site of EPTB. The diagnosis of pleural TB is challenging due to the pauci‐bacillary nature of the disease. Histopathology of thoracoscopically obtained pleural biopsy provides the highest diagnostic yield. The Xpert MTB/RIF assay (Xpert) is a PCR test that can identify both Mycobacterium tuberculosis (MTB) and rifampicin resistance. Currently, there is a lack of clarity regarding the value of Xpert on pleural tissue. We report our experience of using Xpert on thoracoscopic pleural biopsy samples. Methods: We retrospectively reviewed the records of patients who underwent thoracoscopy in our institution over a 1‐year period. Relevant clinical details; indications; and results of tests on pleural tissue and fluid, including histopathology, mycobacterial cultures and Xpert, were extracted. Results: Of the 156 patients who underwent thoracoscopy, 73 (47%) had TB, 66 (42%) malignancy and 17 (11%) other conditions. Histopathology was diagnostic in all the 73 TB patients (100%). The yields of the microbiological tests against histopathology on thoracoscopic biopsy sample and pleural fluid were: pleural tissue Xpert 45%, pleural tissue culture 39%, pleural fluid culture 17% and pleural fluid Xpert 14%. Pleural tissue provided higher yields than fluid in both Xpert and culture ( P < 0.05). Pleural tissue Xpert provided a higher yield than culture and substantially improved yield compared with closed pleural biopsy as we previously reported. Conclusion: Thoracoscopic pleural biopsy results in increased sensitivity on Xpert testing. Abstract : The role of pleural biopsy samples used in the Xpert MTB/RIF test (Xpert) to diagnose tuberculosis (TB) pleural effusion is unclear. We demonstrate an increase in diagnostic sensitivity when the Xpert test is performed on pleural tissue obtained by thoracoscopic biopsy, and it exceeds the yield from pleural fluid Xpert and mycobacterial culture of pleural tissue and fluid.